Self Compassion Training to Increase Resilience in Inmates of Class II A Women's Prison in Pontianak - Puput Makarti; Antonius Johanes Tjahjoanggoro (Analitika: Jurnal Magister Psikologi UMA, 2022)
This study aims to test the effectiveness of self-compassion training to increase resilience. The training provided is based on aspects of self-compassion, namely self kindness, common humanity and mindfulness. The method used is a quasi-experimental one group pre-test post-test design. The training was attended by 15 residents of Class II A Women's Prison in Pontianak who have an age range of 18 to 56 years with the last education being elementary school to bachelor degree. Evaluation is done at the level of reaction, learning, and behavior. Quantitative data was obtained by providing a resilience scale as measured by the Connor-Davidson Resilience Scale (CD-RISC) which consists of 10 items with five choices of answer from very inappropriate to very appropriate. Quantitative data were then analyzed using a paired sample t-test (t = 3,800, p = 0.002 (p < 0.05)). The conclusions of this study indicate that self-compassion training is effective in increasing resilience of the inmates at Class II A Women's Prison in Pontianak.